Adaptive Techniques for Home-based Software DSMs - Whately, Lauro; Pinto, Raquel; Rangarajan, Muralidharan; lftode, Liviu; Bianchini, Ricardo; Amorim, Claudio L. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2001: Anais do XIII Symposium on Computer Architecture and High Performance Computing, 2001)
This paper proposes and evaluates Home-based Adaptive Protocol (HAP), a software distributed shared-memory system. HAP performs two key functions that distinguish it from most other distributed shared-memory systems: detection of sharing patterns and behavior adaptation based on these patterns. Detection consists of identifying any change in the sharing pattern of a shared page. Adaptation consists of using a strategy that is specific to the sharing pattern detected to optimize the performance of the system. More specifically, HAP uses updates to maintain the coherence of single-writer pages, which fall under the migratory and producer-consumer sharing patterns. Invalidations are used to maintain the coherence of multiple-writer pages, which can potentially be falsely shared. As part of HAP's adaptation strategy, we dynamically assign homes to pages based on their sharing patterns. We performed preliminary experiments on an 8-node cluster of PCs. Our results show that the current implementation of HAP substantially improves the performance of single-writer applications in which shared pages are modified in critical sections protected by locks. The results also indicate potential improvement in the performance of applications exhibiting other sharing patterns such as producer-consumer, single-writer between barriers. However, the detection and adaptation techniques for these patterns have to be redesigned to exploit the real performance gains that can be achieved with the adaptive system.